Consumer’s Preference to Buy For Organic and Non Organic Processed Duck Meat In Blitar - Nur Agustin Mardiana; Adiguna S.W. Utama; Nur Aini Mahmudah; Aditya W. Putra (Universitas Dr Soetomo, 2023)
Global food security and health awareness have increased, thus driving demand for organic food. Blitar, one of the duck farming centers on Java Island, has much potential to develop organic farming. However, consumer attitudes and product acceptance of organic farming must be analyzed to develop organic farming. Therefore, this study aimed to identify the factors that determine consumer attitudes and preferences in buying processed organic duck meat. This study used 39 respondents who live in Blitar. This study used the Fishbein method to assess consumers’ beliefs and important levels of attributes of processed duck. The results showed that 74% of respondents were willing to buy organic processed duck meat. Meanwhile, the most important attributes of processed duck products decided by consumers were taste (3,74), packaging (3,62), and aroma (3,61). The three major belief values for organic processed duck products were health factor (3,61), label (3,58), and taste (3,38), while for non-organic processed duck were label (3,72), packaging (3,62), and taste (3,59).